WEWENANG PERAWAT GIGI TERHADAP PELAYANAN KESEHATAN GIGI BERDASARKAN KOMPETENSINYA - Aristia Pradita Widasari Widodo; Dian Kristanti; Jambi Luna M (Program Studi Akuntansi IKOPIN, 2021)
Health service efforts carried out by health workers are activities to maintainand improve health in accordance with medical professional standards, servicestandards and in accordance with their authority. Health workers who cancarry out health efforts need authority, one of which is a dental nurse. A dentalnurse can perform dental and oral nursing care actions as well as limitedmedical actions in the field of dentistry based on delegation from the dentist.Dentists can give part of their authority to dental nurses which are given inwriting and must be in accordance with their educational abilities,competencies and in accordance with the provisions of laws and regulations.The independent authority is exercised by the dental nurse without anydelegation from the dentist, because legally, the dental nurse has the attributionauthority to take action. The existence of the Regulation of the Minister of Health of the Republic of Indonesia Number 20 of 2016 concerning Permits andImplementation of the Practice of Dental and Oral Therapists, cannot beimplemented properly and still causes problems, among others, a dental nursefeels free to take medical actions outside of her competence. Authority exercisedoutside this competence will cause harm to the patient and lead to lawsuits formalpractice or deviations from the performance of a dental nurse's duties